2019
DOI: 10.1080/01426397.2019.1580352
|View full text |Cite
|
Sign up to set email alerts
|

Foraging for identity: the relationships between landscape activities and landscape identity after catastrophic landscape change

Abstract: In this article, we deal with landscape activities in relation to changing landscape identity after a major wildfire in Sweden in 2014. The aim was to investigate the relationships between 22 landscape activities (before the fire) and 2 components (emotion and cognition) of landscape identity (before and after the fire). A total of 656 respondents living nearby the fire area participated in this study. Before the fire, a positive association was found between the activities of enjoying nature and foraging, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Humans bond with physical sites involving psychological, social, historical, cultural, and health dimensions (Knez, 2005;Lewicka, 2008;Lachowycz and Jones, 2013;Butler et al, 2019). These ties act as reminders of significant collective and personal encounters (Knez, 2006;Lewicka, 2008;Wang, 2008;Taylor, 2010;Wheeler, 2014) involving emotional, cognitive, and behavioral operations in how we perceive ourselves as individuals and collectives (Canter, 1997;Casey, 2000;Knez and Thorsson, 2006;Knez, 2014).…”
Section: Place-related Identitymentioning
confidence: 99%
See 3 more Smart Citations
“…Humans bond with physical sites involving psychological, social, historical, cultural, and health dimensions (Knez, 2005;Lewicka, 2008;Lachowycz and Jones, 2013;Butler et al, 2019). These ties act as reminders of significant collective and personal encounters (Knez, 2006;Lewicka, 2008;Wang, 2008;Taylor, 2010;Wheeler, 2014) involving emotional, cognitive, and behavioral operations in how we perceive ourselves as individuals and collectives (Canter, 1997;Casey, 2000;Knez and Thorsson, 2006;Knez, 2014).…”
Section: Place-related Identitymentioning
confidence: 99%
“…The psychological phenomenon of place-related identity also includes information about the surrounding nature (Knez, 2005(Knez, , 2006Knez and Eliasson, 2017;Butler et al, 2019), which has been reported to be associated with: (1) Curative feelings of wellbeing (Korpela, 1989(Korpela, , 1992Korpela and Hartig, 1996;Knez, 2006) for both personal and collective favorite places (Knez and Eliasson, 2017); and (2) Emotional loss of a beloved site after a natural disaster (Knez et al, 2018a;Butler et al, 2019).…”
Section: Place-related Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…Lidskog and Sjödin 2016; Johansson and Bäck 2017), media coverage (Berglez and Lidskog 2017;Johansson and Odén 2018), and perception of change in landscape identity (Butler et al 2018(Butler et al , 2019Knez et al 2018). One methodological ecology-oriented paper using data from the fire area is available (Bohlin et al 2017) but otherwise natural science papers so far are very few (but see Żmihorski et al in press).…”
Section: Limited Research Fundingmentioning
confidence: 99%